Coronary heart disease incidence among non-Western immigrants compared to Danish-born people: effect of country of birth, migrant status, and income. (29th August 2020) - Bo, Anne; Zinckernagel, Line; Krasnik, Allan; Petersen, Jorgen H; Norredam, Marie
Abstract: Background: Increasing global migration has made immigrants' health an important topic worldwide. We examined the effect of country of birth, migrant status (refugee/family-reunified) and income on coronary heart disease (CHD) incidence. Design: This was a historical prospective register-based cohort study. Methods: The study cohort consisted of immigrants above 18 years from non-Western countries who had obtained a residence permit in Denmark as a refugee ( n  = 29, 045) or as a family-reunified immigrant ( n  = 28, 435) from 1 January 1993–31 December 1999 and a Danish-born reference population ( n  = 229, 918). First-time CHD incidence was identified from 1 January 1993–31 December 2007. Incidence ratios for 11 immigrant groups were estimated using Cox regression analysis. Results: Immigrants from Afghanistan, Iraq, Turkey, Eastern Europe and Central Asia, South Asia, the Former Yugoslavia, and the Middle East and North Africa had significantly higher incidences of CHD (hazard ratio (HR) = 1.36; 95% confidence interval (CI): 1.05–1.75 to HR = 2.86; 95% CI: 2.01–4.08) compared with Danish-born people. Immigrants from Somalia, South and Middle America, Sub-Saharan Africa and women from East Asia and the Pacific did not differ significantly from Danish-born people, whereas immigrant men from East Asia and the Pacific had a significantly lower incidence (HR = 0.32; 95% CI: 0.17–0.62). When also including migrant status, the higher incidences were reduced. Refugee men (HR = 1.35; 95% CI: 1.11–1.65) and women (HR = 1.33; 95% CI: 1.08–1.65) had a significantly higher incidence of CHD than family-reunified immigrants. When migrant status and income were included simultaneously, the incidences decreased to an insignificant level for most immigrant groups. Conclusions: Most non-Western immigrant groups had a higher incidence of CHD than Danish-born people. The study revealed that migrant status and income are important underlying mechanisms of the effect of country of birth on CHD.